Strategic Enterprise Architecture Management Challenges, Best Practices, and Future Developments - Ahlemann, Frederik; Stettiner, Eric.; Messerschmidt, Marcus; Legner, Christine; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The discipline of Enterprise Architecture Management (EAM) deals with the alignment of business and information systems architectures. While EAM has long been regarded as a discipline for IT managers this book takes a different stance: It explains how top executives can use EAM for leveraging their strategic planning and controlling processes and how EAM can contribute to sustainable competitive advantage. Based on the analysis of best practices from eight leading European companies from various industries the book presents crucial elements of successful EAM. It outlines what executives need to do in terms of governance, processes, methodologies and culture in order to bring their management to the next level. Beyond this, the book points how EAM might develop in the next decade allowing today$1 (Bs managers to prepare for the future of architecture management.s
An EAM Navigator -- The EAM agenda for the CxO -- EAM governance and organisation -- Embedding EAM in strategic planning -- Embedding EAM into the Project Lifecycle -- Embedding EAM in operation and monitoring -- EA Frameworks, Modelling and Tools -- People, Adoption and Introduction of EAM -- EAM 2020 - The future of the Discipline.
Keywords: Economics; Industrial management; Business planning; Management information systems; Economics/Management Science; Organization/Planning.; Business Information Systems; Business/Management Science, general; Management/Business for Professionals